Clinical Experiences with Closed Incisional Negative Pressure Wound Treatment on Various Anatomic Locations - Ozkan, Burak (Cureus, 2020)
Background Closed incisional negative pressure wound treatment (ciNPWT) is one of the promising methods for the prevention of complications in surgical incisions. The mechanisms of ciNPWT have previously been elucidated and in this series, we demonstrate various, as of yet, underreported uses for the technology. Our aim is to share our experience with ciNPWT on various anatomic sites with novel indications.  Materials and methods ciNPWT was used in 24 patients. The mean age was 49.6. All the incisions were sutured, clean, and non-infected. Patients’ sex, age, comorbidities, anatomic location of the wound, and the indications for ciNPWT were recorded. Results The mean number of applications was three per patient. One suture dehiscence after one session of ciNPWT was encountered in a flap donor site of an infant operated for meningomyelocele. Late-term seroma and hematoma formation were encountered in two patients. No surgical site infection, wound dehiscence, and ciNPWT related complications were seen in other patients. The majority of the applications were on the trunk, lower extremity, pelvis, upper extremity, and scalp respectively. Indications for ciNPWT utilization were preventing dehiscence, seroma, and hematoma formation in the majority of the patients. Conclusion ciNPWT is reliable and effective in the prevention of post-operative wound dehiscence and surgical site infections. It can be used safely in various locations and different indications for preventingcomplications such as preventing dehiscence in revision surgeries, cerebrospinal fluid (CSF) fistula formation in the scalp, and wound breakdown in chronic corticosteroid use,